Substitution of foreign protein sequences into a chimeric toxin composed of transforming growth factor alpha and Pseudomonas exotoxin. - Debinski, W (1991)
TGF alpha-PE40 is a chimeric toxin made by replacing domain Ia of Pseudomonas exotoxin (PE) with transforming growth factor alpha (TGF alpha). We have now replaced a portion of domain Ib of PE with different polypeptides or an extra domain III of PE in transforming growth factor alpha-PE40 and maintained cell killing. Thus, TGF alpha-PE40 can be used to transport foreign protein sequences into the cytosol of cells.